Rhodococcus equi peritonitis in continuous ambulatory peritoneal dialysis: a first in Australia. (5th October 2015) - Azzam, Omar; Crowe, Amy; Sajiv, Cherian; Pawar, Basant
Abstract : A 33-year-old Caucasian man with end-stage renal disease secondary to biopsy-proven IgA nephropathy, managed with continuous ambulatory peritoneal dialysis (PD), presented with PD-related peritonitis, the causal organism being a non-branching Gram-positive bacillus, Rhodococcus equi . Initial empirical Gram positive and negative coverage with cefazolin and ceftazidime was unsuccessful, but following isolation of the organism, and conversion to intraperitoneal vancomycin and oral ciprofloxacin, the peritonitis episode resolved. At day 10, vancomycin was switched to azithromycin for a total of 6 weeks of antimicrobial therapy. The PD catheter was preserved, and the patient remained peritonitis-free at 6 months of follow-up.